Separation of dipetroselin from the coriander extracts / Ibtisam Abdul Wahab and Hannis Fadzillah Mohsin - Abdul Wahab, Ibtisam; Mohsin, Fadzillah (UiTM Press for the Institute of Research Management & Innovation (IRMI), Universiti Teknologi MARA, 2019)
This research is about the natural product of coriander, or the Coriandrumspecies. The bioactive molecules and the health effects of this plant areconstantly discussed. This paper is parallel with those publications,investigating the composition of the herb. The results of current studyindicates that the Coriandrum seed is a source of fatty acids. From thepublications, petroselinic acid or (6Z)-octadecenoic acid, is the major fattyacid in the coriander extracts. Previous articles reported on coriander’schemical constituents, biological activities of the coriander’s seeds andleaves, as well as the coriander products in the retail. Indeed, corianderhas a lot of uses either as a traditional medicines or spices. Different formsof coriander samples were subjected to a simple maceration by usingchloroform. From the chromatographic purification of the seed crudeextract, its component could include anisaldehyde, as one of the aromaticaldehyde. It is concluded that the lipid-containing fraction of the corianderseed could also consist of dipetroselin, a diglyceride.